2018
DOI: 10.1096/fasebj.2018.32.1_supplement.657.14
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime imaging of compartmental pH dynamics using red fluorescent protein sensors in live cells

Abstract: pH regulation plays a crucial role in protein function, cell metabolism, intracellular degradation, and a wide range of other physiological processes. Monitoring perturbations in local pH environments due to cellular activities or diseases, such as increased neuron activity, receptor trafficking, or extracellular acidosis in a tumor microenvironment, would better our understanding of disease pathology. Live‐cell imaging with fluorescent protein‐based sensors allows us to monitor broad pH changes; however, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been shown that the magnitude of the emission lifetime may changes when a fluorescent probe binds to a target that could affect its environment. 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the magnitude of the emission lifetime may changes when a fluorescent probe binds to a target that could affect its environment. 45 …”
Section: Resultsmentioning
confidence: 99%
“…Excited state lifetime measurements evaluate an absolute length scale (on the nanometre range), 37 and, as such, imaging assays using FLIM techniques are less vulnerable to factors such scattered light, photobleaching, nonuniform illumination of the probe, light path length, or laser intensity variations as these can normally be 'gated' out or easily corrected for. Therefore, 2P FLIM has been widely used in imaging cellular protein interactions [38][39][40] and conformational changes, 41 viscosity, 42,43 temperature, 44 pH, 45 ions 46 and oxygen concentrations. 47,48 FLIM generated images based on the differences in the exponential decay rate of the fluorescence from a fluorescent sample on a pixel-by-pixel basis, whereby very high resolution at the diffraction limited level can be obtained.…”
Section: Rsc Chemical Biology Papermentioning
confidence: 99%
See 1 more Smart Citation